Kepemimpinan Transformasional dalam Mewujudkan Budaya Madrasah Berkualitas di Madrasah Aliyah Istimewa Amanatul Ummah Pacet Mojokerto - El Rizaq, Agung Dwi Bahtiar (Pascasarjana IAIN Kudus, 2021)
Quality education as a major milestone in realizing human resources to survive in the midst of the globalization challenges. This study aims to interpret the principals transformational leadership style in building quality culture at the MA Istimewa (MAI) Amanatul Ummah Pacet Mojokerto. This study uses a qualitative method by descriptive approach. The primary and secondary data were analyzed using Miles and Huberman technique. The result of this study is the transformational leadership model applied at the Amanatul Ummah including; the implementation of leader grand idea as a reference for various programs and improving the quality of educator resources; then the madrasah culture formed through intracurricular activities that prioritize the quality of learning, extracurricular activities to explore the students talents and interests, implementation of madrasa culture to instil al-karimah character, and involve the community by asking suggestion. This study recommends to explore the integration of mu’adalah and formal education system learning in pesantren.